Serum anti-Mullerian hormone and homocysteine in premenopausal females with and without cardiovascular disease - Khan, Huma; Gupta, Madhur M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The objective of this study is to assess the association of anti-Mullerian hormone (AMH) and homocysteine (Hcy) levels in premenopausal females with and without cardiovascular disease. Methods: A case control study was conducted in premenopausal, menopausal and normal fertile females (n=30) with and without cardiovascular disease in a tertiary care hospital and research centre in central India. Fasting sample obtained was assessed for AMH and Hcy levels. Results were compared and data was analyzed. Results: The levels of AMH and Hcy were significantly altered in premenopausal and menopausal females as compared to normal fertile females. Moreover, there was a weak correlation when intergroup comparison was made between the parameters in females with and without cardiovascular disease. Conclusions: A prospective study with a larger sample size to assess levels of AMH need to be performed to provide insight in premenopausal females for the early detection cardiovascular disease.